1991
DOI: 10.1111/j.1476-5381.1991.tb09799.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological specificity of N‐methyl‐d‐aspartate receptors in rat cerebral cortex: correspondence between radioligand binding and electrophysiological measurements

Abstract: 1 The pharmacological specificity of N-methyl-D-aspartate (NMDA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…In addition, glycine also inhibited the binding in all areas. The effect was antagonized by the glycine antagonist, 7-CKA, in all regions, indicating that the possibility of negative allosteric modulation of [3H]-CGP 39653 binding, through the activation of the associated strychnine-insensitive glycine site of the NMDA receptor channel complex (Mugnaini et al, 1993) (Lynch et al, 1993;Marti et al, 1993;Laurie & Seeburg, 1994 (Buller et al, 1994) strictly paralleled that of the mRNA encoding for the NR2A subunit (Laurie & Seeburg, 1994 CPP and CGS 19755 which were more in accord with the low affinity site (Fagg et al, 1990;Grimwood et al, 1991 (Monaghan et al, 1988;Buller et al, 1994). It may be noteworthy that in our data, because of the different allosteric modulation, basal [3H]-CGP 39653 binding was already partially inhibited by the endogenous glycine to a greater extent in striatum with respect to the cerebral cortex and the thalamus.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, glycine also inhibited the binding in all areas. The effect was antagonized by the glycine antagonist, 7-CKA, in all regions, indicating that the possibility of negative allosteric modulation of [3H]-CGP 39653 binding, through the activation of the associated strychnine-insensitive glycine site of the NMDA receptor channel complex (Mugnaini et al, 1993) (Lynch et al, 1993;Marti et al, 1993;Laurie & Seeburg, 1994 (Buller et al, 1994) strictly paralleled that of the mRNA encoding for the NR2A subunit (Laurie & Seeburg, 1994 CPP and CGS 19755 which were more in accord with the low affinity site (Fagg et al, 1990;Grimwood et al, 1991 (Monaghan et al, 1988;Buller et al, 1994). It may be noteworthy that in our data, because of the different allosteric modulation, basal [3H]-CGP 39653 binding was already partially inhibited by the endogenous glycine to a greater extent in striatum with respect to the cerebral cortex and the thalamus.…”
Section: Discussionmentioning
confidence: 95%
“…Measurements of the KD Of L-glutamate binding to purified membranes have led to values ranging from 120 to 620 nm (see Grimwood, Foster & Kemp, 1991). This is in the range expected if the NMDA receptor in purified membranes is in a state comparable to that it adopts in 'stabilized' outside-out patches, in which the KD of binding would reflect predominantly binding to the desensitized states.…”
mentioning
confidence: 98%
“…*p i 0.05 for difference from control. tabolism in this system, the concentrations of the antagonists used in these experiments should have blocked their corresponding receptors by over 90% (Pearce et al, 1985;Honor6 et al, 1988;Ivins and Molinoff, 1990;Grimwood et al, 1991). Although high levels of PI hydrolysis were stimulated by D -A s~ in the current studies, previous studies in adult rats suggested that D-As~ does not stimulate PI metabolism (Nicoletti et al, 1986b).…”
Section: Resultsmentioning
confidence: 99%